Disruption of diabetes and hypertension care during the COVID-19 pandemic and recovery approaches in the Latin America and Caribbean region: a scoping review protocol - Jabakhanji, Samira Barbara; Ogungbe, Oluwabunmi; Angell, Sonia Y.; Appel, Lawrence; Byrne, David; Mehta, Roopa; McCaffrey, John; Rosman, Lori; Gregg, Edward W.; Matsushita, Kunihiro (BMJ open, 2024)
Introduction The COVID-19 pandemic significantly disrupted primary healthcare globally, with particular impacts on diabetes and hypertension care. This review will examine the impact of pandemic disruptions of diabetes and hypertension care services and the evidence for interventions to mitigate or reverse pandemic disruptions in the Latin America and Caribbean (LAC) region. - Methods and analyses This scoping review will examine care delivery disruption and approaches for recovery of primary healthcare in the LAC region during the COVID-19 pandemic, focusing on diabetes and hypertension awareness, detection, treatment and control. Guided by Arksey and O’Malley’s scoping review methodology framework, this protocol adheres to the Joanna Briggs Institute guidelines for scoping review protocols and the Preferred Reporting Items for Systematic Reviews and Meta-Analyses guidance for protocol development and scoping reviews. We searched MEDLINE, CINAHL, Global Health, Embase, Cochrane, Scopus, Web of Science and LILACS for peer-reviewed literature published from 2020 to 12 December 2022 in English, Spanish or Portuguese. Studies will be considered eligible if reporting data on pandemic disruptions to primary care services within LAC, or interventions implemented to mitigate or reverse pandemic disruptions globally. Studies on COVID-19 or acute care will be excluded. Two reviewers will independently screen each title/abstract for eligibility, screen full texts of titles/abstracts deemed relevant and extract data from eligible full-text publications. Conflicts will be resolved through discussion and with the help of a third reviewer. Appropriate analytical techniques will be employed to synthesise the data, for example, frequency counts and descriptive statistics. Quality will be assessed using the Newcastle Ottawa Quality Assessment Scale. - Ethics and dissemination No ethics approval was needed as this is a scoping review of published literature. Results will be disseminated in a report to the World Bank and the Pan American Health Organization, in peer-reviewed scientific journals, and at national and international conferences.
Gesehen am 18.06.2024